2003
DOI: 10.1211/0022357021387
|View full text |Cite
|
Sign up to set email alerts
|

Rofecoxib: an update on physicochemical, pharmaceutical, pharmacodynamic and pharmacokinetic aspects

Abstract: Rofecoxib (MK-966) is a new generation non-steroidal anti-inflammatory agent (NSAID) that exhibits promising anti-inflammatory, analgesic and antipyretic activity. It selectively inhibits cyclooxygenase (COX)-2 isoenzyme in a dose-dependent manner in man. No significant inhibition of COX-1 is observed with rofecoxib up to doses of 1000 mg. The pharmacokinetics of rofecoxib has been found to be complex and variable. Mean oral bioavailability after single dose of rofecoxib (12.5, 25 or 50 mg) is 93% with t m a x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 230 publications
(172 reference statements)
0
22
0
Order By: Relevance
“…The estimated MADs of these two compounds based on the highest absorption rate suggested in the literature are much lower than the clinical dose because of very high dose number (18). However, it is reported that rofecoxib (29) and imiquimod (30) showed complete oral absorption in clinical study. The Cmax of these two compounds was also unaltered in the presence of food, suggesting lack of food effect on dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated MADs of these two compounds based on the highest absorption rate suggested in the literature are much lower than the clinical dose because of very high dose number (18). However, it is reported that rofecoxib (29) and imiquimod (30) showed complete oral absorption in clinical study. The Cmax of these two compounds was also unaltered in the presence of food, suggesting lack of food effect on dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…But, no clinically signifi cant drug interaction has been reported for rofecoxib except that it reverses their salt-wasting effects of diuretics (Ahuja et al, 2003). Kaminski et al (1998) had earlier reported that non-steroidal anti-infl ammatory drugs (NSAIDs) increased the protective effect of valproate and phenytoin in epilepsy without altering the total plasma levels of valproate or diphenylhydantoin (Kaminski et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…But, no clinically significant drug interaction has been reported for rofecoxib except with diuretics, where it reverses their salt-wasting effect and thus can be clinically exploited in electrolyte-wasting disorders. (Ahuja et al, 2003). Moreover, in one study done by Kaminski et al (1998), non-steroidal anti-infl ammatory agents (NSAIDs) increased the protective effect of valproate in epilepsy and when checked the plasma levels of drugs were studied, the total plasma levels of valproate and free plasma levels of diphenylhydantoin remained unchanged in the presence of all the NSAIDs examined, showing no pharmacokinetic interactions (Kaminski et al, 1998).…”
Section: Figmentioning
confidence: 99%